Globalization, Political Regimes and International Environmental Commitment - Thomas Bernauer; Anna Kalbhenn; Vally Koubi; Gabriele Ruoff (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2008)
In this paper we are interested in the relationship between globalization, political institutions (notably, democracy) and international environmental commitments. This relationship has been the subject of a particularly intensive debate and the existing literature offers a wide range of partly competing claims with respect to the driving forces of international environmental cooperation. While some authors argue that democracy and globalization tend to promote international efforts to mitigate or resolve environmental problems others have challenged these propositions theoretically and empirically. We argue that existing studies suffer from three weaknesses. First, they are based on very small samples of multilateral environmental treaties in respect to which commitment is coded (usually in terms of treaty ratification) and are cross-sectional. Second, they examine the effects of globalization and political institutions on international environmental policy separately and ignore potential joint effects. Third, they ignore interdependency (diffusion) effects - i.e., they do not account for the possibility that international commitment of one country is likely to depend on what other countries and specific types or groups of other countries do (network effects). Based on a new panel dataset that includes the commitments of 180 countries with regard to international environmentaltreaties from 1902 to 2005 we study whether and how international economic and political integration, and domestic political institutions jointly affect international environmental commitments. We also study interdependency (network) effects on our dependent variable. Our preliminary results show that the net effect of democracy on environmental cooperation is rather diffuse and so is the effect of economic integration (trade openness).
Keywords: 330; Globalization; democracy; international cooperation/commitments; environment